Severe autogenously fecal peritonitis in ageing Wistar rats. Response to intravenous meropenem - Mascena,Guilherme Veras (2014)
PURPOSE: To evaluate the treatment outcome of severe peritonitis in rats with increasing age.METHODS:Thirty Wistar rats stratified in three groups: group I - six month-old; group II - 12 month-old; and group III - 18 month-old, underwent autogenously fecal peritonitis (6 ml/kg rat), and were treated with intravenous meropenem. The survival animals were followed-up for 45 days. The variables were expressed by their mean and standard error of the mean (SEM). p<0.05 was used for rejecting the null hypothesis. The study was approved by the Ethics Committee.RESULTS: There was a significant increase in the mortality and morbidity in elderly rats. Of interest, even among young survival rats presenting with severe residual abscesses both in the abdomen and thorax cavities, they present an almost normal life.CONCLUSIONS:The treatment of severe autogenously fecal peritonitis with intravenous meropenem reached reasonable results in rats with six and twelve months of age, even considering residual abscesses on abdomen and thorax cavities. However, the great majority (80%) of elderly rats could not overcome the initial severe infectious challenge, proving that ageing is a very important risk factor for impairing immune response. Thus, sepsis remains a challenging situation, especially in elderly.